Participation and awareness of citizens in drought plans - Rodríguez Perea A. (Drought management: scientific and technological innovations, 2008)
The drought plans are essential tools in water planning. However, in a large part of them, citizen participation is reflected in a theoretical way and with little ability to actual involvement. These plans are reactive to crises in the water deficit and not envisage a scenario in which the drought is presented as a fact of life but erratic. Moreover, the involvement of the media in raising public awareness about the value of water is essential at the present time and is not sufficiently covered in such plans.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)